2012
DOI: 10.1007/s11745-012-3674-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Extraction of Saturated Fatty Acids but not Omega‐3 Fatty Acids from Sheep Red Blood Cells Using a One‐Step Extraction Procedure

Abstract: Several methods are available to extract total lipid and methylate fatty acids from a range of samples including red blood cells (RBC). Fatty acid analysis of human RBC can be undertaken using a two-step extraction and methylation or a combined one-step extraction and methylation procedure. The lipid composition of sheep RBC differs significantly from that of humans and may affect their extraction. The purpose of the current study was to examine the efficiency of extraction of lipid and detection of fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Adjusting BHT concentrations in the hexane solvent present during derivatization in the direct method had no effect, suggesting that extraction differences rather than lipid peroxidation might be responsible for differences in PUFA yields (data not shown). In a similar comparison for red blood cells, more saturated fatty acids were extracted with a direct method than with Folch but not MUFAs or PUFAs (Clayton et al 2012). Conversely, two comparative studies using marine animal material reported improved recovery of PUFAs in direct methods relative to conventional two-step methods, however (Abdulkadir and Tsuchiya 2008; Indarti et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Adjusting BHT concentrations in the hexane solvent present during derivatization in the direct method had no effect, suggesting that extraction differences rather than lipid peroxidation might be responsible for differences in PUFA yields (data not shown). In a similar comparison for red blood cells, more saturated fatty acids were extracted with a direct method than with Folch but not MUFAs or PUFAs (Clayton et al 2012). Conversely, two comparative studies using marine animal material reported improved recovery of PUFAs in direct methods relative to conventional two-step methods, however (Abdulkadir and Tsuchiya 2008; Indarti et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fatty acid analysis of human red blood cell can be determined by a two-step extraction and methylation or a combined one-step extraction and methylation procedure [17,20,25,26].…”
Section: Methods Of Determining Fatty Acid Compositionmentioning
confidence: 99%
“…A vivid picture of the long-term dietary intake, with particular emphasis on long-chain omega-3 polyunsaturated fatty acids, can be obtained by deducing the concentrations of fatty acids in red blood cells (RBCs) [17,18]. The fatty acids present in erythrocyte membrane phospholipids can be incorporated during de novo synthesis or via exchange from the pool of fatty acids in the plasma [12].…”
Section: Fatty Acid Composition In Biological Systemsmentioning
confidence: 99%
See 2 more Smart Citations